Evolved Sustainable Building Engineering in Vernacular Architecture of Kurdistan - Rostam, Dilan M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2017)
Vernacular Architecture in Kurdistan is a widely understudied subject. Whilst rapid development is taking place across the Kurdistan region of Iraq, the lack of a clear knowledge of local building traditions has led to the loss of locality and engineering adaptability of newly developed buildings. Advances in mass development in the Kurdistan region need to have clear signs of Kurdish cultural heritage alongside lasting and sustainable solutions. The study of mountain villages of rural Kurdistan will provide valuable information about sustainable building practices as well as cultural values in regional settlements. This in turn will be useful in finding more adoptable green choices in the region and identifying the characteristics of the evolved building engineering of these indigenous settlements. This paper will first describes the characteristics of the evolved engineering and sustainable adoptions of Kurdish historical building traditions through selected site visits to Kurdish vernacular settlements and then analyses the building customs of rural communities of Kurdistan for possible adoption in contemporary developments.